Hydrochemistry : basic concepts and exercises - Worch, Eckhard, 1951- (De Gruyter graduate., 2015)
Quality and usability of water is determined by its dissolved or suspended constituents. This book provides an overview of the physical and chemical processes in aquatic systems that determine the input, output, or transformation of water constituents. Emphasis is placed on the mathematical description of relevant reaction equilibria in aquatic systems and the practical application of equilibrium relationships. An outstanding text and exercise book for students in all environmental study programs.